Power and endurance: Polar opposites or willing partners? - Ferguson, C.; Furrer, R.; Murach, K. A.; Hepple, R. T.; Rossiter, H. B. (Medicine & Science in Sports & Exercise, 2025)
Peak neuromuscular power and endurance are distinct qualities of dynamic exercise performance. Dynamometry is used to assess peak neuromuscular power, often during performance across a single joint, for example, isotonic or isokinetic torque, whereas aptitude for endurance exercise may be inferred by measurement of critical power/speed or cardiopulmonary exercise testing to determine, for example, gas exchange threshold (GET), maximum oxygen uptake (VO2max), and exercise economy. Specificity is a critical component of any training program, but oversimplification of the specificity principle has contributed to the view that training adaptations to increase peak neuromuscular power or the ability to endure high power outputs are mutually exclusive, due to (i) differences in the types of motor units recruited and their patterns of activation and (ii) induction of distinct, antagonistic molecular signaling pathways in response to resistance and endurance exercise training (the "interference effect").